Enhancing gravitational wave anisotropies with peaked scalar sources - Gianmassimo Tasinato (Journal of Cosmology and Astroparticle Physics, 2023)
Gravitational wave (GW) backgrounds of cosmological origin are expected to be nearly isotropic, with small anisotropies resembling those of the cosmic microwave background. We analyse the case of a scalar-induced GW background and clarify in the process the relation between two different approaches to calculating GW anisotropies. We focus on GW scenarios sourced by a significantly peaked scalar spectrum, which are frequently considered in the context of primordial black holes production. We show that the resulting GW anisotropies are characterised by a distinct frequency dependence. We explore the observational consequences concentrating on a GW background enhanced in the frequency band of space-based GW detectors. We study the detectability of the signal through both cross-correlations among different space-based GW detectors, and among GW and CMB experiments.